2017
DOI: 10.1103/physrevc.95.045802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strong magnetic fields on the crust-core transition and inner crust of neutron stars

Abstract: The Vlasov equation is used to determine the dispersion relation for the eigenmodes of magnetized nuclear and neutral stellar matter, taking into account the anomalous magnetic moment of nucleons. The formalism is applied to the determination of the dynamical spinodal section, a quantity that gives a good estimation of the crust-core transition in neutron stars. We study the effect of strong magnetic fields, of the order of 10 15 -10 17 G, on the extension of the crust of magnetized neutron stars. The dynamica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 54 publications
7
76
0
2
Order By: Relevance
“…The width of the crust monotonically increases with the magnetic field for all studied models, and it seems to be very well correlated with the star radius, a stiffer EoS producing a thicker crust. Conversely, the region where successive homogeneous and inhomogeneous layers are expected [34,35,36], measured by the variable ∆l crust , seems to decrease with increasing stiffness. Figure 10: Circumferential radius vs gravitational mass of neutron stars endowed with strong magnetic fields computed using the MM for TM1 EoS.…”
Section: Model Dependence Of the Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The width of the crust monotonically increases with the magnetic field for all studied models, and it seems to be very well correlated with the star radius, a stiffer EoS producing a thicker crust. Conversely, the region where successive homogeneous and inhomogeneous layers are expected [34,35,36], measured by the variable ∆l crust , seems to decrease with increasing stiffness. Figure 10: Circumferential radius vs gravitational mass of neutron stars endowed with strong magnetic fields computed using the MM for TM1 EoS.…”
Section: Model Dependence Of the Resultsmentioning
confidence: 91%
“…Another interesting calculation [33] points to quite a large crust (2.4 Km) for a 1.4 M ⊙ neutron star, with non-negligible consequences on the cooling mechanism and on the emission of gravitational waves. The crust-core region of magnetars has recently been studied within the relativistic mean field model framework [34,35,36]. In these works, the effects of strong magnetic fields (10 15 − 10 17 G) on the instability region have been investigated with the help of the Vlasov formalism used to determine the dynamical spinodals.…”
Section: Introductionmentioning
confidence: 99%
“…[26] it was shown that models with cross-interaction on the mesonic fields are capable of producing maximum masses in the range of 1.93 ≤ M/M ⊙ ≤ 2.05, at least when the effect of the hyperons are disregarded, and there are 11 parameterizations in this situation. The selected parameterizations are included in this class, and are the IU-FSU [40] and the NL3ωρ [41] parameterizations.…”
Section: Hadronic Phasementioning
confidence: 99%
“…作为软γ射线和不 规则X射线源的磁星, 其表面磁场强度可达10 12 ∼ 论 文 究工作则相对较少 [19∼23] . 最近, 文献 [20,22,24] [19] 采用Skyrme相互作 用和Thomas-Fermi(TF)近似方法研究了强磁场环境 中 仅 包 含 球 形 原 子 核 的 内 壳 层 性 质. de Lima等 人 [23] 采用RMF理论模型和TF近似方法研究了质子 分支比Y p = 0.1和Y p = 0.3时的原子核pasta相结构, 计算中忽略了核子的反常磁矩. 因此有必要采用更 为全面的理论模型和方法对中子星在强磁场环境中 满足β平衡条件的pasta相结构和壳核相变性质进行 详细的研究.…”
unclassified